A unified stress-strain model for LRS FRP-confined concrete columns with square and circular cross-sections. (15th March 2022) - Yuan, Wan-Ying; Han, Qiang; Bai, Yu-Lei
Highlights: A unified design-oriented model was established for LRS FRP-confined square and circular concrete columns. The model has simple expressions and avoids the discontinuity of predictions for columns with different cross-sections. A threshold confinement level that determines the hardening or softening compressive behavior was established. The effective rupture strain of FRP and the equivalent diameter were reviewed and examined. Seven existing theoretical confinement models were evaluated. Abstract: Large rupture strain (LRS) fiber-reinforced polymer (FRP) composites with an ultimate elongation of greater than 5% offer superior deformation and energy dissipation abilities over traditional carbon or glass FRP when used them in lateral confinement of concrete under the same confinement level. However, a flexible model for predicting the stress-strain relationship of concrete columns confined with LRS FRP is not yet perfectly developed, especially for noncircular columns experiencing nonuniform confining stress. Accordingly, an extensive database of LRS FRP-confined square and circular concrete columns with corner radius ratios varying from 0 to 1 was employed to establish a unified stress-strain model. This model not only includes the determinations of key points, but also attempts to define the threshold confinement level to distinguish the post-peak strain-hardening and strain-softening behaviors. The mathematical expression of the model is simple; it also avoids discontinuities in the prediction of different cross-sections. The proposed model is verified to be accurate in predicting the complete stress-strain curves of LRS FRP-confined square and circular concrete columns with hardening and softening behaviors. In addition, it outperforms the existing theoretical models in predicting the ultimate strength and the ultimate axial strain.